Ensino Artístico Especializado da Música: : Avaliação da Pertinência de uma Possível Reestruturação - Moreira, Marta (2021)
In Specialized Artistic Music Teaching (SAMT) the precariousness of work conditions and the instability of educativecontexts are factors that make the pedagogical work developed more difficult. It was sought to understand what are thestructural problems that affect this subsystem, placing the emphasis on the grounds SAMT is organized in, and in whatway that organization helps/harms the accomplishing of its goals. Through a comparative study, aiming to understandboth the evolution of SAMT over the last few decades, and its substantiation in the public and private teaching models,gaps and discrepancies were diagnosed. The bibliographic review of several evaluation reports of the artistic teachingshows that an effective response to these problems was not achieved. It was thus assumed relevant to secure somerestructuring suggestions, presenting an example that embodies both its generic side and the specialized one.